Clinical and Microbiologic Outcomes of Ceramic Laminate Veneers Bonded to Teeth Without a Finish Line: 1-year Results of a Prospective Study - de Oliveira, Danila [UNESP]; Souza, Fernando I. [UNESP]; Caixeta, Mariana T. [UNESP]; Duque, Cristiane [UNESP]; Oliveira, Sandra H. P. [UNESP]; Rocha, Eduardo P. [UNESP] (Quintessence Publishing, 2023)
Purpose: To evaluate changes in the periodontium of teeth restored with ultrathin (0.2 to 0.39 mm) ceramic laminate veneers (CLVs) placed subgingivally without a finish line compared to the same teeth before restorative treatment and to nonrestored antagonist teeth in healthy periodontium patients. Materials and Methods: A total of 73 CLVs were bonded onto the enamel surface of teeth without a finish line and with the cervical margin placed about 0.5 mm subgingivally. The gingival crevicular fluid was collected before bonding (baseline) and at 7, 180, and 365 days after bonding to quantify S mitis, P intermedia, and P gingivalis by quantitative polymerase chain reaction analysis. Visible plaque index (VPI), bleeding on probing (BOP), probing depth (PD), clinical attachment loss (CAL), gingival recession (GR), and marginal adaptation were evaluated from baseline to 365 days in both groups. Results: No statistically significant differences were observed in VPI, PD, or BOP at any time point in the intragroup or intergroup comparisons (P >.05). All restorations obtained the alpha concept for marginal adaptation (ie, the restoration margin remained ideal at all time points). There was a statistically significant difference for S mitis between 180 and 365 days (P =.03). No statistically significant difference was observed for P gingivalis at any time point (P >.05). Conclusion: The periodontium in the restored group showed a clinical behavior similar to baseline. Overcontouring of the ultrathin (up to 0.39 mm) CLV, similar to the cementoenamel junction convexity, did not contribute to plaque accumulation or changes in the oral microbiota of patients with a healthy periodontium and proper oral hygiene instruction.